Age- and sex-related variations of individual retinal layer thickness in the foveal center of healthy eyes. (June 2022) - Bringmann, Andreas; Barth, Thomas; Wiedemann, Renate; Wiedemann, Peter
Abstract: Alterations of the visual function during life are associated with changes in the morphological parameters of the outer retinal layers of the fovea. We evaluated age- and sex-related variations of the mean thicknesses of the different retinal layers at the central foveola which provides the maximal visual acuity. The vertical expansions of the following structures were measured on spectral-domain optical coherence tomographic images of 2944 healthy eyes of 1990 subjects with ages between 5 and 85 years: the total thickness of the retinal tissue, the thickness of the retinal pigment epithelium, the lengths of photoreceptors (receptor segments), photoreceptor outer segments (POS), and photoreceptor inner segments (PIS), and the thicknesses of the ellipsoid zone (EZ), myoid zone (MZ), external limiting membrane, outer nuclear layer, Henle fiber layer, and the horizontal layer of the Müller cell cone. We found diverse morphologies of the central photoreceptor layer with different thicknesses of the EZ and interdigitation zone lines. The mean total thickness of the retinal tissue at the central foveola showed three periods: it increased between 5 and about 41 years of age, displayed a plateau until about 52 years, and decreased continuously thereafter. Photoreceptors, POS, and PIS displayed their maximal mean lengths between 5 and about 36 years of age; the lengths decreased continuously between 36 and 85 years of age. Whereas the mean thickness of the EZ did not alter across the life span, the mean thickness of MZ displayed three periods: it increased between 5 and about 21 years of age, showed a plateau until about 36 years, and decreased considerably thereafter. Sex differences were observed for five parameters in eyes of subjects aging between 55 and 85 years. We suggest that the MZ thickness reflects the level of the metabolic activity of photoreceptors. The increase in the MZ thickness, likely reflecting increasing metabolic activity of photoreceptors, might contribute to the improvement of visual function in young subjects. The decrease of the MZ thickness in the fovea of elderly might reflect a decrease of the metabolic activity perhaps resulting from mitochondrial dysfunction which is known to occur in photoreceptors of aged eyes. Highlights: Individual layers of the foveal center show distinct thickness alterations with age. The photoreceptor length shows a plateau between 5 and 36 years of age. The thickness of the ellipsoid zone does not alter across the life span. The thickness of the myoid zone shows a plateau between 21 and 36 years of age. The thickness of the myoid zone likely reflects the metabolic activity of photoreceptors.